Efficacy of Different Organophosphate Pesticides against Jassid Feeding on Okra (Abelmoschus esculentus) - Eijaz, Saleem; Khan, M. Farhanullah; Mahmood, Khalid; Shaukat, Sohail; Siddiqui, Afaq Ahmed (Journal of Basic & Applied Sciences, 2012)
Field studies were conducted for the determination of efficacy of different organophosphate pesticides viz Profenofos, Dimethoate , Acephate and Malathion against jassid (Amrasca devastans) feeding on okra crop. Seeds of okra crop were planted in randomized block design with 3 replicates. The pretreatment observations were recorded at 24 hour before spray, while, the post-treatment observations were taken after 1, 2, 3,4,5,6 and 7 days of treatment. The crop was sprayed four times repeatedly with 7 day interval during the experimental period. The results revealed that all of the tested pesticides reduced the population of Amrasca devastans except Profenofos. Though the Profenofos was unable to reduce the pest population but it was able to somewhat control the further proliferation of pest. In contrary Dimethoate was found as the most effective against the jassid with significant reduction in pest population against the control and other treatments.The results obtained from the research concluded that the organophosphate pesticides including Dimethoate, Acephate, and Malathion were found effective for controlling the jassid population feeding on okra but the low dose of pesticides including Profenfos were found ineffective.